2012
DOI: 10.1016/j.cirp.2012.03.126
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fluid lubrication mechanisms in metal forming at mesoscopic scale

Abstract: The lubricant entrapment and escape phenomena in metal forming are studied experimentally as well as numerically. Experiments are carried out in strip reduction of aluminium sheet applying a transparent die to study the fluid flow between mesoscopic cavities. The numerical analysis involves two computation steps. The first one is a fully coupled fluid-structure Finite Element computation, where pockets in the surface are plastically deformed leading to the pressurization of the entrapped fluid. The second step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…The testing device is illustrated on Figure 3. Figure 3: Experimental testing device with its intrinsic parameters, after [5].…”
Section: Methodsmentioning
confidence: 99%
“…The testing device is illustrated on Figure 3. Figure 3: Experimental testing device with its intrinsic parameters, after [5].…”
Section: Methodsmentioning
confidence: 99%
“…have been carried out [7][8][9][10][11]. In the present study, the experimental results produced by Dubar et al [6] are used to analyse the e ects of lubricant escape on the final roughness of the worked surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…This study also showed strong changes in the worked surface roughness where MPHSL and MPHDL occur, but has not been investigated further. More recently, Dubar et al [6] carried out similar kind of experiments, with the same testing device as [5], but with triangular sectioned grooves as lubricant reservoirs, machined by means of Electro Discharge Machining (EDM). The aim of this technique was to avoid metal banks due to the indentation process, to avoid any lubricant escape perturbation due to these banks and to confer true plane strain properties to the analysis, including the lubricant escape.…”
Section: Introductionmentioning
confidence: 99%
“…Dubois and coworkers [13][14][15] used a fluid-solid coupling approach implemented in a FE software to model lubricant exchanges between consecutive pockets in plane strip drawing. The model limitation is the direct connexion between two consecutive cavities from the beginning of the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the section of the link is not calculated by the simulation. This team also conducted some experimental work: their experimental device was similar to the one of Bech [3] using triangular sectioned grooves as lubricant reservoirs [14]. They employed a new method based on the estimation of roughness peaks curvature estimation [16,17] to identify the regions where local changes due to MPH lubrication occurred [18].…”
Section: Introductionmentioning
confidence: 99%